(untitled) (Experimental biology, 2018)
Biologically active compounds (BAC) of plants are represented by various classes of organic compounds and are a prospective raw material for developing therapeutic and preventive remedies. There are more than 6,000 plant species on the territory of the Republic of Kazakhstan that might become a source of raw materials for development and production of new domestic original phyto-pharmaceuticals. Therefore, testing of biologically active compounds extracted from Kazakhstan’s wild-growing plants is a timely and promising task. It was determined that the roots of two wild plants of Kazakhstan flora - Salvia deserta and Vexibia alopecuroides contain biologically active compounds with high a) antibacterial and antifungicidal activities estimated by the IC50 index, b) anti-inflammatory activity estimated by the ability to inhibit production of nitric oxide, c) therapeutically significant antioxidant potential with respect to the ABTS.+ radical cations. Crude extracts of biologically active compounds from the roots of S. deserta and V. alopecuroides plants that have the above mentioned activities were obtained by maceration with methylene chloride, purified into individual compounds using flash and gas chromatography. It was determined that 9 individual compounds that revealed biological activity were isolated from Vexibia alopecuroides roots’ extract, which belongs to flavonoids, and 4 compounds were isolated from Salvia deserta roots’ extract, which belongs to diterpenoids. Individual compounds isolated from Salvia deserta and Vexibia alopecuroides roots’ extract showed antimicrobial activity against S. aureus, Methicillin-resistant S. aureus, P. aeruginosa, C. glabrata, C. krusei, C. albicans with an IC50 index within the range of < 0, 8 to 13.38 μg / ml. It allows to consider them as potential candidates for development of new-galenic phyto-pharmaceuticals. Key words: biologically active compounds, crude extracts, antimicrobial activity, Salvia deserta, Vexibia alopecuroides.